External environmental and insects factor for attraction of Edible Bird Nest Swiftlet (Aerodramus fuciphagus) in Sarawak - Alvin, Amos; Lokman, Hakim Idris; Jalila, Abu; Nur Mahiza, Md. Isa; Ibitoye, Emmanuel Busayo (Universiti Malaysia Sarawak, 2023)
Edible Bird Nest (EBN) swiftlet industry plays a significant role in the economic growth in Sarawak. This study aimed at identifying both the external environmental factors and types of insects that are important for a successful swiftlet farmhouse (SFH). For this purpose, a total of 21 SFHs from the southern areas of Sarawak were selected. The external environmental factors of SFH and the type of insects present in relation to the number of EBN swiftlet populations were analysed using descriptive statistics. The results showed that external environmental locations, namely rural and remote areas, were highly selected (71.42%) for the construction of SFHs (p<0.05) compared to the other location categories, as analysed using the Kruskal-Wallis test. Significant relationships (p<0.05) were observed between environmental factors (habitat origin and predation) and the population of EBN swiftlets in the SFHs. Large densities of the EBN swiftlet populations were found in SFHs located in areas with fewer disturbances. The highest population of insect types in most SFHs was Diptera (52.38%). This study can be used as a guideline for swiftlet ranchers looking to startup their EBN swiftlet farming.